Hydro aerobics as means for physical state improvement of female students - Balamutova N.M; Babadganjan V.V (Kharkov National Pedagogical University, 2013)
The questions of organization and conducting studies were considered by using system of hydro aerobics exercises for improving physical training of female students. Sixty female students took part in the experiment. All the tested girls were divided into two groups, 30 persons each. The tested group of female students made aerobic exercises on the dry land according to a plan. The female students of experimental group made hydro aerobics exercises according to the programme. Several methods were used: anthropometry, control methods of the functional parameters of the body, testing of the physical training indicators, methods of mathematical statistics. The reliable positive improvements of cardiovascular and respiratory systems were in the experimental group of the girls. The effect of the reliable decrease of fat mass of the tested female students was exposed among anthropometrical characteristics.